The DNA damage checkpoint: A tale from budding yeast - Pizzul, Paolo; Casari, Erika; Gnugnoli, Marco; Rinaldi, Carlo; Corallo, Flavio; Longhese, Maria Pia (Frontiers in Genetics, 2022)
Studies performed in the yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe have led the way in defining the DNA damage checkpoint and in identifying most of the proteins involved in this regulatory network, which turned out to have structural and functional equivalents in humans. Subsequent experiments revealed that the checkpoint is an elaborate signal transduction pathway that has the ability to sense and signal the presence of damaged DNA and transduce this information to influence a multifaceted cellular response that is essential for cancer avoidance. This review focuses on the work that was done in Saccharomyces cerevisiae to articulate the checkpoint concept, to identify its players and the mechanisms of activation and deactivation.